the question is wrong.
the question should be:
tanx tany - ex cosx + y' sec2y = 0 equation1
solution: this equation is of the form:
f'(y) y' + P f(y) = Q where P and Q are functions of x.
here, P= tanx and Q = excosx , f(y)=tany
let tany=v such that sec2y. y' = v'
equation1 becomes v'+ vtanx = excosx equation2
this equation is linear in v and x
so, integrating factor= "\\left(e^{\\smash{\\int P dx}}\\right)" = "\\left(e^{\\smash{\\int tanx dx}}\\right)" = secx
equation2 becomes v.secx = "\\int" ex cosx secs dx + constant'c'
v.secx = ex + c
tany.secx = ex +c
Comments
Leave a comment